Taurisolo®, a Grape Pomace Polyphenol Nutraceutical Reducing the Levels of Serum Biomarkers Associated With Atherosclerosis - Annunziata, Giuseppe; Ciampaglia, Roberto; Maisto, Maria; D'Avino, Maria; Caruso, Domenico; Tenore, Gian Carlo; Novellino, Ettore (Frontiers in Cardiovascular Medicine, 2021)
Trimethylamine-N-oxide (TMAO) is a gut microbiota-derived metabolite recognized as strongly related to cardiovascular diseases (CVD), mainly increasing the risk of atherosclerosis development. Currently, no pharmacological approaches have been licensed for reduction of TMAO serum levels and conventional anti-atherosclerosis treatments only target the traditional risk factors, and the cardiovascular risk (CVR) still persist. This underlines the need to find novel targeted strategies for management of atherosclerosis. In this study we tested the ability of a novel nutraceutical formulation based on grape pomace polyphenols (Taurisolo®) in reducing both the serum levels of TMAO and oxidative stress-related biomarkers in humans (n=213). After chronic treatment with Taurisolo® we observed significantly reduced levels of TMAO (-49.78% and -75.80%, after 4-week and 8-week treatment, respectively), oxidized LDL (oxLDL; -43.12% and -65.05%, after 4-week and 8-week treatment, respectively) and reactive oxygen species (D-ROMs; -34.37% and -49.68%, after 4-week and 8-week treatment, respectively). On the other hand, no significant changes were observed in control group. Such promising, the results observed allow indicating Taurisolo® as an effective nutraceutical strategy for prevention of atherosclerosis. Clinical trial registration: This study is listed on the ISRCTN registry with ID ISRCTN10794277 (doi: 10.1186/ISRCTN10794277)